2016
DOI: 10.5114/pjp.2016.65861
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer with different ERG status may show different FOXP3-positive cell numbers

Abstract: Prostatic carcinoma is the most frequent cancer in males in the Western world. A significant proportion of these cancers have a recurrent translocation involving ETS family genes, which leads to the overexpression of ERG transcription factor. Prostate cancers, which bear this mutation, differ in a number of features, including tumor microenvironment. One of the components of the tumor microenvironment is FOXP3 positive lymphocytes, which may participate in breaking immunosurveillance and promoting tumor growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…At least for ERG, these data appear to be reproducible in that they are similar to results from two previously published studies in European or European-American cohorts, both of which demonstrated a similar association between ERG expression and CD3+ T-cell density ( 21 , 46 ), as well as a separate study reporting a similar association with FOXP3+ cell density ( 47 ). However, the mechanism of this association remains unclear.…”
Section: Discussionsupporting
confidence: 88%
“…At least for ERG, these data appear to be reproducible in that they are similar to results from two previously published studies in European or European-American cohorts, both of which demonstrated a similar association between ERG expression and CD3+ T-cell density ( 21 , 46 ), as well as a separate study reporting a similar association with FOXP3+ cell density ( 47 ). However, the mechanism of this association remains unclear.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, Gr-MDSC show a higher production of reactive oxygen species (ROS) when compared to Mo-MDSC, which, on the other hand, comparing to Gr-MDSC display increased expression of inducible nitric oxide synthase (NOS2) and NO production [19]. MDSC could also induce T regulatory cells, which are often correlated with cancer progression [20].…”
Section: Introductionmentioning
confidence: 99%
“…We previously identified several differences between the microenvironment of ERG+ and ERG-PC. In our material, the ERG+ cancers had a significantly denser microvascular network [10] and higher concentrations of FOXP3+ regulatory lymphocytes [7], mast cells [8] and other inflammatory cells [9]. Some of the diffe rences between ERG+ and ERG-PC were observed by other authors as well [29,30].…”
Section: A B a Bmentioning
confidence: 59%
“…In our previous studies, we estimated the proportion of ERG+ cases in Poland at 46%; we also revealed several differences in tumor morphology and in particular the microenvironment [7][8][9][10]. Some studies have suggested that miRNAs may influence the biology of PC, including its invasiveness and response to antiandrogen treatment [11,12].…”
Section: Introductionmentioning
confidence: 99%